2024
DOI: 10.18063/ijb.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Artificial vascularized scaffolds for 3D-tissue regeneration — a report of the ArtiVasc 3D Project

Abstract: Abstract:The aim of this paper is to raise awareness of the ArtiVasc 3D project and its findings. Vascularization is one of the most important and highly challenging issues in the development of soft tissue. It is necessary to supply cells with nutrition within a multilayer tissue, for example in artificial skin. Research on artificial skin is driven by an increasing demand for two main applications. Firstly, for the field of regenerative medicine, the aim is to provide patients with implants or grafts to repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…gelatin, agarose, pluronic F-127) that are printed into a bulk hydrogel for later removal from the main matrix [e.g., collagen I, photopolymerized poly-(ethylene glycol) diacrylate], followed by perfusion of the produced channels in a subtractive manufacturing approach (Lee et al, 2010 ; Bertassoni et al, 2014 ). Over the past 4 years, the expansion of biofabrication techniques has aided production of vessels including bioprinting (Kolesky et al, 2014 ; Bibb et al, 2016 ), subtractive manufacturing with sacrificial electrospun polymers (Lee et al, 2016a ) as well as many other approaches which are summarized in a review by Frueh et al ( 2017 ). In fact, 3D skin constructs produced with vascular (Marino et al, 2014 ) and lymphatic networks (Marino et al, 2014 ; Gibot et al, 2017 ) are possible.…”
Section: Physiological Skin Model In 3dmentioning
confidence: 99%
“…gelatin, agarose, pluronic F-127) that are printed into a bulk hydrogel for later removal from the main matrix [e.g., collagen I, photopolymerized poly-(ethylene glycol) diacrylate], followed by perfusion of the produced channels in a subtractive manufacturing approach (Lee et al, 2010 ; Bertassoni et al, 2014 ). Over the past 4 years, the expansion of biofabrication techniques has aided production of vessels including bioprinting (Kolesky et al, 2014 ; Bibb et al, 2016 ), subtractive manufacturing with sacrificial electrospun polymers (Lee et al, 2016a ) as well as many other approaches which are summarized in a review by Frueh et al ( 2017 ). In fact, 3D skin constructs produced with vascular (Marino et al, 2014 ) and lymphatic networks (Marino et al, 2014 ; Gibot et al, 2017 ) are possible.…”
Section: Physiological Skin Model In 3dmentioning
confidence: 99%
“… 1 Nevertheless, developing whole organs, for example, to replace a heart or just a blood vessel, actually suffers from missing scaffolds which provide the mechanical and geometrical properties to support cell growth and tissue maturation. 2 Nowadays, three-dimensional (3D) bioprinting is one of the most promising technologies for the tailored production of scaffolds. Several rapid prototyping technologies used for 3D bioprinting, for example, fused deposition modeling, 3 laser-assisted bioprinting, 4 or stereolithography 2 show their benefit in implant printing, because they allow for controlled geometries and adapted mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Nowadays, three-dimensional (3D) bioprinting is one of the most promising technologies for the tailored production of scaffolds. Several rapid prototyping technologies used for 3D bioprinting, for example, fused deposition modeling, 3 laser-assisted bioprinting, 4 or stereolithography 2 show their benefit in implant printing, because they allow for controlled geometries and adapted mechanical properties. 5 Besides process controlling, the material development itself is important to get materials fulfilling all the demanding requirements of tissues and organs, for example, being biocompatible and providing the right mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Leong et al reported a simple and efficient method for making 3D nanofibrous scaffolds [9] . Finally, Bibb et al presented a detailed report on the European ArtiVasc 3D project and discussed the successes and lessons that had been learnt [10] .…”
mentioning
confidence: 99%